USEFUL TEACHING METHODS FOR ESL LEARNERS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article explores effective and practical teaching methods for learners of English as a Second Language (ESL). As the number of ESL students continues to rise globally, it is essential for educators to apply methods that promote communication, engagement, and real-world application. The article discusses six key approaches: Communicative Language Teaching, Task-Based Learning, Total Physical Response, the Lexical Approach, integration of technology, and Differentiated Instruction. Real-life examples are provided to illustrate how these methods improve language skills, motivation, and fluency.